A Review on Properties, Synthesis, Surface Functionalization and Application of Nanodiamonds for Antimicrobial Activity - Tyagi, Vandana; Chandra, Amrish; Dhankhar, Neelam; Tyagi, Bhavna (Current Nanomaterials, 2022)
Diamond is a metastable carbon allotrope. Microdiamonds are monocrystalline diamonds with particle sizes of less than 100 nm that have been explored over the last few decades. Nanodiamonds are particularly appealing to provide a variety of possible applications due to their superior mechanical and optical qualities, wide surface area, ease of bioconjugation, and high biocompatibility. In recent years, NDs have gotten a lot of attention in nanomedicine, and some significant progress has been made. The methods for creating various kinds of nanodiamonds are generalized, including detonation, CVD, hydrothermal and High-Pressure, High-Temperature Microdiamond Milling procedures. The characteristics, properties, synthesis, structure and surface functionalization, and applications of nanodiamonds for antimicrobial activity are discussed in this review paper.
Keywords: antimicrobial